Impact of selenium biofortification on production characteristics of forages grown following standard management practices in Oregon - Hall, Jean A.; Bobe, Gerd; Filley, Shelby J.; Bohle, Mylen G.; Pirelli, Gene J.; Wang, Guogie; Davis, T. Zane; Bañuelos, Gary S. (Frontiers in Plant Science, 2023)
Low selenium (Se) concentrations in soils and plants pose a health risk for herbivores consuming locally-grown forages. Previous studies have shown that Se concentrations in forages can be increased using soil-applied selenate amendments. However, the effects of foliar selenate amendments applied with traditional nitrogen-phosphorus-potassium-sulfur (NPKS) fertilizers on forage yields, and nutrient contents, and agronomic efficiencies are unknown. Using a split plot design, we determined the effects of springtime sodium selenate foliar amendment rates (0, 45, and 90 g Se ha-1) and NPKS application (none, NPK for grasses/PK for alfalfa, and NPKS/PKS fertilization at amounts adapted to meet local forage and soil requirements) on forage growth and nitrogen, sulfur, and Se concentrations, yields, and agronomic efficiencies. This 2-year study was conducted across Oregon on four representative forage fields: orchardgrass (Dactylis glomerata L.) in Terrebonne (central Oregon), grass-clover mixture in Roseburg (southwestern Oregon), and both grass mixture and alfalfa (Medicago sativa L.) fields in Union (eastern Oregon). Grasses grew poorly and were low in nitrogen content without NPK fertilization. Fertilization with NPK/PK promoted forage growth, increased forage nitrogen concentrations, and had to be co-applied with sulfur when plant available sulfur was low. Without Se amendment, forage Se concentrations were low and further decreased with NPKS/PKS fertilization. Selenate amendment linearly increased forage Se concentration without adversely affecting forage yields, nitrogen and sulfur concentrations, and nitrogen and sulfur agronomic efficiencies. Importantly, sulfur fertilization did not interfere with Se uptake in Se amended plots. In conclusion, co-application of NPKS/PKS fertilizer and foliar sodium selenate in springtime is an effective strategy to increase forage total Se concentrations, while maintaining optimal growth and quality of Oregon forages.